PENGARUH RETURN ON ASSETS, LEVERAGE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE DI BURSA EFEK INDONESIA - Sitanggang, Elfrida; Banjarnahor, Haposan (EDUTECH CONSULTANT, 2020)
The difference in interest between the government and the company as a taxpayer, causes companies to try to pay as little tax as possible. The greater the income earned means the greater the tax burden to be paid, this condition causes companies to find ways to minimize the tax burden. The purpose of this study is to examine the effect of Return on Assets, Leverage and Corporate Social Responsibility, on Tax Avoidance on the Indonesia Stock Exchange. The population in this study is mining companies listed on the Indonesia Stock Exchange as many as 49 companies. The number of samples was determined by the purposive sampling method, the sample data obtained were 18 sample companies. The analytical method used is multiple linear regression method, with the results of research showing that partially return on assets has a significant negative effect on tax, while leverage and corporate social responsibility have no effect on tax avoidance. Simultaneously, return on assets, leverage and corporate social responsibility have a significant effect on tax avoidance.